2015
DOI: 10.1016/j.jot.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Bone defect animal models for testing efficacy of bone substitute biomaterials

Abstract: SummaryLarge bone defects are serious complications that are most commonly caused by extensive trauma, tumour, infection, or congenital musculoskeletal disorders. If nonunion occurs, implantation for repairing bone defects with biomaterials developed as a defect filler, which can promote bone regeneration, is essential. In order to evaluate biomaterials to be developed as bone substitutes for bone defect repair, it is essential to establish clinically relevant in vitro and in vivo testing models for investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
245
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(273 citation statements)
references
References 104 publications
4
245
0
5
Order By: Relevance
“…Thereupon, the size of the bone tunnel needed drilling during ACL reconstruction operation could be smaller, which is a favorable factor for bone regeneration. 60 This could be another advantage for UHMWPE application in artificial ligament needed to be investigated further.…”
mentioning
confidence: 99%
“…Thereupon, the size of the bone tunnel needed drilling during ACL reconstruction operation could be smaller, which is a favorable factor for bone regeneration. 60 This could be another advantage for UHMWPE application in artificial ligament needed to be investigated further.…”
mentioning
confidence: 99%
“…In a recent review, Li et al. discussed available animal models for alveolar bone regeneration . The authors concluded that most studies fail to discuss the grounds for choosing a specific animal model and the clinical indications that the model simulates.…”
Section: Discussionmentioning
confidence: 99%
“…The available in vivo ABR models are mostly large animal ones, such as the calvaria models in rabbits and rats, and alveolar bone models in rats, rabbits, pigs, and dogs . These models provide valuable information regarding the strength and limitations of ABR materials and modalities.…”
mentioning
confidence: 99%
“…For practical purposes, if there is no more than 30% of the mineralization area after 52 weeks, lifelong incomplete bone healing is to be assumed [32]. The incapacity of natural healing when left untreated represents the negative control, so that the osteogenic potential of the material being tested can be considered unequivocal.…”
Section: Preclinical Trialsmentioning
confidence: 99%